Malay Women in Tiang Seri Tegak Berlima by Noordin Hassan: (Perempuan Melayu dalam Tiang Seri Tegak Berlima Karya Noordin Hassan) (Malay Literature, 2017)
In the theatre script of Tiang Seri Tegak Berlima, it was made known that the men in Malay society are strong and powerful. The role they played was not just restricted to aspects of religion, in fact, it encompassed culture, social, economy and even the political aspects of the society. This situation becomes an important issue in the script written by Dato' Noordin Hassan. Apart from explaining the nature of men, this script also discusses the symbolic positioning of Malay women through the character of Siti Muhsinat. With reference to this character in the script, this paper discusses the issue of Malay women's positioning and the role they play in society, as well as society's response towards Malay women's ability to perform their symbolic roles. To address these two issues, this article employs the theory of critical feminism through the mode of qualitative narrative analysis in order to reveal that men tend to utilize cultural and religious symbols as tools to dominate women.Keywords: Malay women, positioning of the Malay Women, society's recognition, critical feminism